Microbiota-Associated Biofilm Regulation Leads to Vibrio cholerae Resistance Against Intestinal Environmental Stress - Cho, Jennifer Y.; Liu, Rui; Hsiao, Ansel (Frontiers in Cellular and Infection Microbiology, 2022)
The commensal microbes of the gut microbiota make important contributions to host defense against gastrointestinal pathogens, including Vibrio cholerae, the etiologic agent of cholera. As interindividual microbiota variation drives individual differences in infection susceptibility, we examined both host and V. cholerae gene expression during infection of suckling mice transplanted with different model human commensal communities, including an infection-susceptible configuration representing communities damaged by recurrent diarrhea and malnutrition in cholera endemic areas and a representative infection-resistant microbiota characteristic of healthy individuals. In comparison to colonization of animals with resistant microbiota, animals bearing susceptible microbiota challenged with V. cholerae downregulate genes associated with generation of reactive oxygen/nitrogen stress, while V. cholerae in these animals upregulates biofilm-associated genes. We show that V. cholerae in susceptible microbe infection contexts are more resistant to oxidative stress and inhibitory bile metabolites generated by the action of commensal microbes and that both phenotypes are dependent on biofilm-associated genes, including vpsL. We also show that susceptible and infection-resistant microbes drive different bile acid compositions in vivo by the action of bile salt hydrolase enzymes. Taken together, these findings provide a better understanding of how the microbiota uses multiple mechanisms to modulate the infection-associated host environment encountered by V. cholerae, leading to commensal-dependent differences in infection susceptibility.